لغة الإعلام وأثرها التداولي في تشكيل الوعي الجمعي الاجتماعي : جائحة كورونا 19 في قناة المملكة بالأردن أنموزجا - بني ياسين، سجود عمر صالح (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This study aimed to identify the impact of pragmatics in the language of media and social collective awareness on the subject of the Corona pandemic (Coved -19) in the "Almamlaka TV'' in Jordan, and to clarify the general characteristics that should be available in the language of collective media, and to highlight the impact of the language of collective media on collective social awareness. The study relied on the pragmatic approach and the analytical deliberative approach, and the study sample consisted of ( 40) individuals from the Jordanian community. The results showed that most of the study sample watched Almamlaka TV with a percentage of (85%), and the results showed that most of the study sample members had unanimously agreed that most of the awareness-raising efforts of the Corona Virus pandemic in Almamlaka TV contributed to preventing infection with the Coronavirus by a percentage of (80%), and that the program that the study sample members follow in the Kingdom channel to obtain information about the Corona virus is the program (Sawt Almamlaka) with a percentage of (65%). The results indicated that the extent to which the Kingdom channel followed up for the purposes of health education about the Corona virus came at a high level, and the extent to which the programs of the Kingdom channel were used to obtain information about the Corona virus came at a high level. The results showed that the impact of the Kingdom channel programs on health awareness about the Corona virus came to a high level, and that the impact of the "Voice of the Kingdom" program on people's convictions and behaviors about the Corona virus, as the program specialized in following up on the Corona file, came at a high level. The study recommended working on devising new and innovative methods and methods for raising issues of public concern, including health issues, and conducting recorded television interviews that clarify citizens' views on societal and health issues and answer them and correct the public's misconceptions.